Radiation-induced transformation of defects in CaF2, SrF2, and BaF2 - Zavadovskaya E. K.; Lisitsyn V. M. Viktor Mikhailovich; Baranov A. I.; Fedorov V. A.; Stepanov V. G. (1973, 1973)
В фонде НТБ ТПУ отсутствует